Safeguarding Indigenous Heritage in the Anthropocene: A Transnational Comparative Study of the Northwest Territories, Canada, and Northern Chile - Haboucha, Rebecca (University of Cambridge, 2020)
Climate change has been widely recognised as one of the most urgent and growing threats to natural and cultural heritage in the twenty-first century, and the indelible impact of humanity has led to the definition of a new geological epoch, the Anthropocene. Indigenous peoples are disproportionately affected by natural and human-induced changes to the environment. Their vulnerability is exacerbated by centuries of cultural and territorial disenfranchisement within settler-colonial nations. This dissertation aims at understanding Indigenous perceptions of heritage in the face of climate change and its intersection with the impacts of settler- colonialism. It analyses how these on-the-ground perceptions can, in turn, inform heritage organisations and contribute to safeguarding the many facets of tangible and intangible Indigenous heritage for future generations in the Anthropocene. This is accomplished through a comparative, transnational case study of two communities each from the Dehcho First Nations in the Northwest Territories, Canada, and the Aymara and Quechua peoples in northern Chile. I use a multi-method approach consisting of semi-structured interviews, oral histories and participant observation. The data is complemented by environmental and heritage legislation and grey literature at multiple organisational scales for both case studies. Three lines of enquiry are explored through an applied comparative thematic analysis: i) the perceptions of climate change and associated land loss/change among Indigenous groups and how this impacts each group’s notions of challenges to its cultural identity; ii) the intersection of the effects of post- colonialism, ongoing industrial activities and climate change on the intergenerational transmission of ancestral knowledge and notions of place attachment; and iii) how international, national and regional political and sociocultural rhetoric on environmental and heritage conservation affect local, grassroots considerations for safeguarding heritage. The similarities and ...